Ethical principles for judges (Canadian Judicial Council, 2021)
As the Canadian Judicial Council marks its 50th anniversary of service to Canadians, it is timely that we have revised and modernized Ethical Principles for Judges. From their first publication in 1998, these principles have laid out the ethical frame of reference to which all judges aspire: judicial independence, integrity and respect, diligence and competence, equality and impartiality